Impact of Digitalization on Financial Performance of Commercial Banks in Nepal - Ranjitkar, Abiral (Nepalese Journal of Business, 2024)
The study examines the effect of digitalization on the financial performance of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are DD/TT/SWIFT fees income, credit card/ ATM issuance fees income, DD/TT/SWIFT fees expenses, VISA card and master card fees expenses, number of ATMs, and bank size. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of digitalization on the financial performance of Nepalese commercial banks. The study showed that Credit Card/ATM issuance fees income has a negative impact on return on assets. It means that increase in Credit Card/ATM issuance fees income leads to decrease in return on assets. Similarly, number of ATMs has a positive impact on return on equity. It means that increase in number of ATMs leads to increase in return on equity. Likewise, Credit Card/ATM issuance fees income has a positive impact on return on equity. It means that increase in Credit Card/ATM issuance fees income leads to increase in return on equity. In addition, DD/TT/SWIFT fees expenses have a negative impact on return on assets. It means that increase in DD/TT/SWIFT fees expenses leads to decrease in return on assets. Moreover, VISA Card and Master Card fees expenses has a negative impact on return on assets. It means that increase in VISA Card and Master Card fees expenses leads to decrease in return on assets. Further, DD/TT/SWIFT fees expenses have a negative impact on return on assets. It means that increase in DD/TT/SWIFT fees expenses leads to decrease in return on assets. Similarly, bank size has a positive impact on return on assets. It means that increase in bank size leads to increase in return on assets.